Silent struggles: help-seeking barriers for sexual difficulties among adults 50+ in Czechia - Gore-Gorszewska, Gabriela; Ševčíková, Anna; Bártová, Klára; Krejčová, Lucie; Kalenská, Lucie; Androvičová, Renáta; Weiss, Petr; Klapilová, Kateřina (Frontiers in Psychology, 2025)
Although sexual problems become more common with age, older adults rarely seek professional help. Understanding why is key to supporting sexual health in aging populations. This study assessed the prevalence of sexual difficulties, help-seeking behavior, and reasons for not seeking help among Czech adults aged 50–75, using nationally representative data from the 2023/2024 CzechSex survey (n = 2,927; 53% men). Logistic regression analyses examined the predictor role of sociodemographic factors, sexual activity frequency, sexual ageism, and distress over sexual problems on help-seeking. Lifetime sexual difficulties were reported by 59% of respondents, and 31% experienced them in the past 12 months. Among those with persistent issues, only 7.6% sought counseling or other professional help. Women were significantly more likely than men not to seek help (OR = 1.64, 95% CI [1.04, 2.61], p < 0.05); lower distress was also associated with non-help-seeking (OR = 0.68, 95% CI [0.54, 0.86], p < 0.001). The most common reasons for not seeking help were perceiving problems as not bothersome, followed by shame, embarrassment, and difficulty communicating (personal/emotional barriers). Systemic barriers (e.g., lack of services, long wait times) were rarely reported. Overall, help-seeking for sexual problems is uncommon in this age group, and personal barriers outweigh institutional ones, posing a challenge for effectively targeting no-help seekers and designing effective interventions.